Kepuasan Peserta Diklat Terhadap Penggunaan Mentimeter Sebagai Metode Pembelajaran Latsar CPNS Milenial Kabupaten Kampar - Megasari, Embung (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2022)
Participants in the Basic Training for Candidates for Civil Servants at BPSDM Riau Province are millennials, attached to technology, digital learning applications, and provide satisfaction to them, in this case using Mentimeter as a learning application. In a quasi-experimental way, this study describes the perception of the participant's satisfaction scale on the use of Mentimeter as a learning application for the Millennial Generation Civil Servant Latsar Class E Class E, Kampar Regency at BPSDM Riau Province. Satisfaction scale is measured through tangibles, reliability, responsiveness, assurance, and empathy. This finding proves that as a millennial generation learning application, the satisfaction of CPNS Latsar participants with the use of Mentimeter is at the "Very Satisfactory" level because the mean value of satisfaction in each dimension is on a scale of 4.30 - 5.00. The use of a Mentimeter is also appropriate because it can answer the challenges and developments of the times that are attached to information and digital technology. Utilizing Mentimeter implies that it is important for education and training providers, especially BPSDM Riau Province to always maintain satisfaction and improve learning service innovation according to the needs of millennial generation CPNS Latsar participants. The next recommendation is very possible to evaluate digital learning so that the Mentimeter application can be effectively used by various groups of learners.